A diabetic patient increased premature ventricular contractions after using liraglutide: a case report - Huang, Lilan; Yu, He; Fang, Ying (Frontiers in Cardiovascular Medicine, 2024)
The common adverse reactions of liraglutide are hypoglycemia and gastrointestinal reactions. This case reports a patient with type 2 diabetes mellitus who had an increase in ventricular premature beats after using liraglutide and a decrease in ventricular premature beats after stopping liraglutide, suggesting that clinicians should rule out the possibility of drug-related adverse reactions when using liraglutide in the treatment of diabetes mellitus complicated with coronary heart disease and arrhythmia.